Influence of Chromophore Length and Acceptor Groups on the Optical Properties of Rigidified Merocyanine Dyes. Issue 2 (30th December 2013) - Kreß, Katharina Christina; Fischer, Thomas; Stumpe, Joachim; Frey, Wolfgang; Raith, Melanie; Beiraghi, Omid; Eichhorn, S. Holger; Tussetschläger, Stefan; Laschat, Sabine
Abstract: Invited for this month's cover are the three collaborating groups from the University of Stuttgart and the Fraunhofer Institute for Applied Polymer Research in Potsdam, both from Germany as well as the University of Windsor, Canada. The cover picture shows the shift of frontier orbital energies and symmetries upon excitation with light for three different chromophore lengths. Read the full text of the article at 10.1002/cplu.201300308 Abstract : " The development of novel materials for organic light‐emitting diodes and photovoltaic devices is currently one of the hottest topics in chemistry and materials science. " This and more about the story behind the cover in the Cover Profile onpage 184 and about the research itself onpage 223 .